(untitled) (Conferencea, 2023)
The article discusses the issues of the prospects for the use of traditional and non-traditional energy sources that are used in our country today for the consumption of the population, in connection with this, large-scale practical work is being carried out, including the creation of such systems as the establishment of the production of renewable energy sources and their efficient use.